PENGARUH LUAS LAHAN PERTANIAN TERHADAP TINGKAT PENDAPATAN PETANI PADA DESA KEBONAGUNG KECAMATAN BALEREJO KABUPATEN MADIUN - Dianita Maria Roos Pandanwangi (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2014)
The study entitled The Influence Of The Width Of The Agricultural Land To The Farmers Income Level In Kebonagung Village, Balerejo, Madiun has purposes : first, to determine wether the area of the agricultural land has real influence to the farmers income in Kebonagung Village, Balerejo, Madiun. Second, to determine wether the agricultural land partially gives influence to the farmers income in Kebonagung Village Balerejo Madiun.Based on the result of data processing and simultaneously testing on a real level (a) = 5% indicates that the width of agricultural land stimultaneously has influence to the farmers income. It can be seen from the Fcount 523,132 , while Ft 3,97. In the other hand the Sighit 0,000 and Sigprob 0,05. The big influence of the land to the farmers income is shown by Rsquare 0,876. It means that 87% of the farmers income is influenced by the size of the land. While the rest 13% is influenced by another factor which are not included in this study.The result of t test on agricultural land partially give influence it positively gives influence to the farmers income in Kebonagung Village, Balerejo, Madiun. It is proven by the analysis resulth that shows the tcount 232,8727 , ttabel 1,665 or Sighit 0,000 ≤ Sigprob 0,05However , when it’s seen from the regretion equation the size of the land has negative influence. It’s shows by the regretion equation Y = -145966,589 + 1,0105 X. It can be condtuded from the regretion equation, that it the size of the land is increased by 1%. The income of the farmers will be decreased 1,0105 X, while another factor a held constant.